2018
DOI: 10.1155/2018/2645963
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Interleukin-10-592 (-590, -597) C>A Polymorphisms to Periodontitis Susceptibility: An Updated Meta-Analysis Based on 18 Case-Control Studies

Abstract: Introduction The association between interleukin-10- (IL-10-) 592 (-590, -597) C>A polymorphisms and susceptibility to chronic or aggressive periodontitis (CP or AgP) is conflicting. This meta-analysis is aimed at quantitatively estimating the association. Materials and Methods PubMed, Embase, Web of Science, and WANFAN were searched for studies performed prior to January 31, 2018, to collect data for our research. Meta-analysis was performed using RevMan 5.3 or STATA 14.0. Results In total, 18 studies that me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
(80 reference statements)
0
4
0
Order By: Relevance
“…17,18 Four recent meta-analysis reached similar conclusion supporting IL10 polymorphisms as possible biomarkers for PD. 1922…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 Four recent meta-analysis reached similar conclusion supporting IL10 polymorphisms as possible biomarkers for PD. 1922…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Four recent metaanalysis reached similar conclusion supporting IL10 polymorphisms as possible biomarkers for PD. [19][20][21][22] The effect of VDR appeared less consistent among different populations. 23,24 Although increasing number of papers reported association between genetic polymorphisms and PD, the way for their use for diagnostic or prognostic purposes appeared full of obstacles.…”
Section: Discussionmentioning
confidence: 99%
“…In early studies, candidate genes involved in host immunity, inflammation, and tissue remodeling were selected as targets, and their single nucleotide polymorphisms (SNPs) were associated with periodontitis. A number of candidate gene studies showed that IL1A, IL1B, IL4, IL6, IL10, TNFA, FcγR, VDR, TLR2, TLR4, and MMP1 [ 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ] were the main genes associated with periodontal disease. In particular, the IL-1 gene cluster has been analyzed since the early days of studies on periodontal genetics, and SNPs in the IL-1 genes were proposed to be used for genotyping periodontal patients [ 70 , 71 , 72 , 73 ].…”
Section: Examination and Diagnosis For Precision Periodonticsmentioning
confidence: 99%
“…The candidate genes for AgP include, among others, IL-1 and its receptor antagonist ( IL-1RN ), IL-6 and its receptor ( IL-6R ), IL-10 , IL-17A , and IL-18 . As individual case-control studies in various populations reported controversial results, meta-analyses focused on variants in the mentioned genes were performed and their relation to localized, generalized, or both AgP was predicted [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Studies investigating combinations of polymorphisms within specific haplotypes and host genotypes with microbial profiles might provide important information on the pathogenesis of this complex disease [ 31 ].…”
Section: Introductionmentioning
confidence: 99%